Shotgun Proteomics Identifies Active Metabolic Pathways in Bleached Coral Tissue and Intraskeletal Compartments - Axworthy, Jeremy B.; Timmins-Schiffman, Emma; Brown, Tanya; Rodrigues, Lisa J.; Nunn, Brook L.; Padilla-Gamiño, Jacqueline L. (Frontiers in Marine Science, 2022)
Coral bleaching events are increasing with such frequency and intensity that many of the world’s reef-building corals are in peril. Some corals appear to be more resilient after bleaching but the mechanisms underlying their ability to recover from bleaching and persist are not fully understood. We used shotgun proteomics to compare the proteomes of the outer layer (OL) tissue and inner core (IC) tissue and skeleton compartments of experimentally bleached and control (i.e., non-bleached) colonies of Montipora capitata, a perforate Hawaiian species noted for its resilience after bleaching. We identified 2,361 proteins in the OL and IC compartments for both bleached and non-bleached individuals. In the OL of bleached corals, 63 proteins were significantly more abundant and 28 were significantly less abundant compared to the OL of non-bleached corals. In the IC of bleached corals, 22 proteins were significantly more abundant and 17 were significantly less abundant compared to the IC of non-bleached corals. Gene ontology (GO) and pathway analyses revealed metabolic processes that were occurring in bleached corals but not in non-bleached corals. The OL of bleached corals used the glyoxylate cycle to derive carbon from internal storage compounds such as lipids, had a high protein turnover rate, and shifted reliance on nitrogen from ammonia to nitrogen produced from the breakdown of urea and betaine. The IC of bleached corals compartmentalized the shunting of glucose to the pentose phosphate pathway. Bleached corals increased abundances of several antioxidant proteins in both the OL and IC compartments compared to non-bleached corals. These results highlight contrasting strategies for responding to bleaching stress in different compartments of bleached M. capitata and shed light on some potential mechanisms behind bleaching resilience.